PENGEMBANGAN E-MODUL BERBASIS KONTEKSTUAL PADA MATA PELAJARAN IPAS KELAS IV UPT SD NEGERI SIDOTENTREM I - Suharti, Siti (Jurnal Tunas Pendidikan, 2025)
This research uses a type of development research. Research produces contextual based e-modul for science subjects. The test subjects in this research were for class IV students UPT SD Negeri Sidotentrem I. The research model used by ADDIE consisted of the stages of analysis, design, development, implementation and evaluation. The are three data analysis techniques used, e-module validity analysis, e-module effectiveness analysis and e-module practicality analysis. The instrument used to test the level of validity of the e-module is with an expert validation sheet consisting of material experts, media expers and language experts. The instruments used to test the level of practicality of the e-module are student response questionnaire sheets and theacher response questionnaire. The expert validation results showed that the percentage of material experts was 92%, language experts were 85%, and media experts were 86,66% in the very valid category. The studet learning test result obtained a percentage of 90,47% in the effective category. Based on teacher and student responses the precentage obtained were 94% ang 91,16% in the verypractical category.